Предмет: Алгебра,
автор: ntulyaewa2017
Разложите на множители
Ответы
Автор ответа:
0
1)
х⁷ + 9х⁶ - х² - 9х =
= (х⁷ + 9х⁶) - (х² + 9х) =
= х⁶(х+9) - х(х+9) =
= (х+9)(х⁶-х) =
= х(х⁵-1)(х+9)
Можно решить иначе:
х⁷ + 9х⁶ - х² - 9х =
= х(х⁶ + 9х⁵ - х - 9) =
= х((х⁶+9х⁵)-(х+9)) =
= х(х⁵(х+9)-1(х+9)) =
= х(х+9)(х⁵-1)
2)
(a+b)² + 2a + 2b =
= (a+b)² + 2(a + b) =
= (a+b)(a+b+2)
х⁷ + 9х⁶ - х² - 9х =
= (х⁷ + 9х⁶) - (х² + 9х) =
= х⁶(х+9) - х(х+9) =
= (х+9)(х⁶-х) =
= х(х⁵-1)(х+9)
Можно решить иначе:
х⁷ + 9х⁶ - х² - 9х =
= х(х⁶ + 9х⁵ - х - 9) =
= х((х⁶+9х⁵)-(х+9)) =
= х(х⁵(х+9)-1(х+9)) =
= х(х+9)(х⁵-1)
2)
(a+b)² + 2a + 2b =
= (a+b)² + 2(a + b) =
= (a+b)(a+b+2)
Автор ответа:
0
х вынесли из второй скобки (х⁶-х) =х(х⁵-1)
Похожие вопросы
Предмет: Математика,
автор: vitaliklapin08
Предмет: Математика,
автор: anitaasieva27
Предмет: Геометрия,
автор: dasamamkina07
Предмет: Математика,
автор: Аделиночка5445
Предмет: Биология,
автор: Mariam11122004